Chromosome-level genome assembly of the diploid blueberry Vaccinium darrowii provides insights into its subtropical adaptation and cuticle synthesis - Cui, Fuqiang (2022)
Vaccinium darrowii is a subtropical wild blueberry species that has been used to breed economically important southern highbush cultivars. The adaptive traits of V. darrowii to subtropical climates can provide valuable information for breeding blueberry and perhaps other plants, especially against the background of global warming. Here, we assembled the V. darrowii genome into 12 pseudochromosomes using Oxford Nanopore long reads complemented with Hi-C scaffolding technologies, and we predicted 41 815 genes using RNA-sequencing evidence. Syntenic analysis across three Vaccinium species revealed a highly conserved genome structure, with the highest collinearity between V. darrowii and Vaccinium corymbosum. This conserved genome structure may explain the high fertility observed during crossbreeding of V. darrowii with other blueberry cultivars. Analysis of gene expansion and tandem duplication indicated possible roles for defense- and flowering-associated genes in the adaptation of V. darrowii to the subtropics. Putative SOC1 genes in V. darrowii were identified based on phylogeny and expression analysis. Blueberries are covered in a thick cuticle layer and contain anthocyanins, which confer their powdery blue color. Using RNA sequencing, we delineated the cuticle biosynthesis pathways of Vaccinium species in V. darrowii. This result can serve as a reference for breeding berries whose colors are appealing to customers. The V. darrowii reference genome, together with the unique traits of this species, including its diploid genome, short vegetative phase, and high compatibility in hybridization with other blueberries, make V. darrowii a potential research model for blueberry species.